2022
DOI: 10.3390/metabo12050379
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Profiling of Arabidopsis WT, lbr-2-2 and bak1-4 Mutants Following Treatment with Two LPS Chemotypes

Abstract: Plants perceive pathogenic threats from the environment that have evaded preformed barriers through pattern recognition receptors (PRRs) that recognise microbe-associated molecular patterns (MAMPs). The perception of and triggered defence to lipopolysaccharides (LPSs) as a MAMP is well-studied in mammals, but little is known in plants, including the PRR(s). Understanding LPS-induced secondary metabolites and perturbed metabolic pathways in Arabidopsis will be key to generating disease-resistant plants and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…B Phenolic compounds profiling. Heatmap of the major phenolic compounds (identified with available standards (a) or annotated from literature (b: [ 45 ], c: [ 47 ], d: [ 48 ]) in the five species ( Q. pubescens , O. basilicum , P. oceanica , A. thaliana , V. vinifera ). Common logarithm of the peak area means (area/mL) for each condition (five technical replicates) and each metabolite is expressed per one microliter of the extract solution injected (one mg of the starting plant dry material per mL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B Phenolic compounds profiling. Heatmap of the major phenolic compounds (identified with available standards (a) or annotated from literature (b: [ 45 ], c: [ 47 ], d: [ 48 ]) in the five species ( Q. pubescens , O. basilicum , P. oceanica , A. thaliana , V. vinifera ). Common logarithm of the peak area means (area/mL) for each condition (five technical replicates) and each metabolite is expressed per one microliter of the extract solution injected (one mg of the starting plant dry material per mL).…”
Section: Resultsmentioning
confidence: 99%
“…Extraction and UHPLC-ESI-HRMS profiling analysis was carried out according to [ 46 ]. The major phenolic compounds in each species were identified with available standards or annotated with bibliographic data [ 45 48 ]. Common logarithm of the peak area means (> 19,000 area/mL) for each condition (five technical replicates) and for each metabolite expressed per one microliter injected of the extract solution (one mg of the starting plant dry material per mL).…”
Section: Methodsmentioning
confidence: 99%
“…In the same study, SA and JA were also positively correlated with LPS treatment, as we also observed in tomato following treatment with AA (Finnegan et al 2016; Lewis et al 2022). Recent work in A. thaliana wild-type and receptor mutants treated with two chemotypes of LPS showed increases in hydroxycinnamic acid and derivatives and enrichment of the associated phenylpropanoid pathway (Offor et al 2022). Work in tobacco similarly found treatment with LPS, chitosan, and flg22 all induced accumulation of hydroxycinnamic acid and derivatives, and that defense responses elicited by these MAMPs were modulated by both SA and JA (Mhlongo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Flavone 3 -O-methyltransferase 1 identified at 12 h in LPS Pst -treated lbr2-2 is involved in flavonol and lignin biosynthesis process needed for ultraviolet (UV) radiation protection, herbivore feeding deterrent and defence against pathogens [171]. These results suggest that LPS Pst and LPS Xcc triggered the synthesis of enzymes that catalyse the accumulation of defence-related proteins and secondary metabolites [172], in response to bacterial pathogen attacks.…”
Section: Pm-associated Proteins Related To Metabolic Processesmentioning
confidence: 94%